European integration and adjustment in border regions in accession countries - Laura Resmini (European Regional Science Association (ERSA), 2002)
Border regions in accession countries are not the exception but the rule, since they cover almost 66% of the land and account for 58% of total population. The fall of the Berlin wall has put borders in a state of flux, with changes occurring in the physical location and perhaps their economic significance as well: the "core" markets moved from East to West, raising new challenges and opportunities for development for western border regions, and serious concerns for regions located along the Eastern border, potentially more sensitive to the collapse of the CMEA and the former Soviet Union. This paper aims at exploring and analysing on a comparative basis the impact of the East enlargement of the EU on border regions in Bulgaria, Estonia, Hungary, Romania and Slovenia. These five countries have different development levels and geographical co-ordinates that make their comparative analysis interesting. Hungary and Slovenia are relatively more advanced than Estonia, Bulgaria and Romania. In addition, Estonia is a North European country sharing its border with Finland, while Hungary is a Central European country showing common border with Austria. Slovenia and Bulgaria are Southern European countries bordering, respectively, with Italy and Austria, and Greece. Romania does not share any border with the EU-15. As a result, Hungary and Slovenia seem have the advantage of geographical proximity to Western European core countries, while the others do not. In order to achieve the overall objective, the paper will first provide a definition and identification of border regions in the candidate countries. Every state border and border region, in fact, is unique: its meaning and significance may change dramatically through space and time. Secondly, it will provide a descriptive analysis of their relative position within each country and with respect to the EU-15 average. Thirdly, it will develop an econometric model able to analyse the determinants of regional specialisation in different type of regions (internal vs border; western versus eastern border regions, etc.). In particular, the work will explore how the ongoing process of economic integration with the EU is affecting regional specialisation and which are the winning and loosing regions in this process, in terms of regional growth prospects. This classification will be used to evaluate the likely distributional implications of enlargement for the accession countries under considerations. The overall empirical results, though limited in some counts, may serve as a reminder of border regions' challenges. They allow to identify present patterns and trends, and represent a good baseline to make inference on what changes border regions in candidate countries might expect the integration process to bring.
Keywords: 330